International tourists' perception on tourism facilities at selected tourism destination in Kuala Lumpur - Fatin Liana binti Ismail (Kulliyyah of Architecture and Environmental Design , International Islamic University Malaysia, 2013)
The main objective of this research is to study the international tourists' perception towards tourism facilities and tourism sites in Kuala Lumpur. It is to examine their level of satisfaction on facilities and tourism destinations during their visits. The research concentrates on four aspects; analyses the tourists profile and their interest of visit, tourists' perception towards facilities and tourism sites management, and their opinion on improving the facilities in Kuala Lumpur. The questionnaire survey was distributed with a total of 120 responses at various major nodes in Kuala Lumpur which are located near public transportation routes and also other destinations which spotted as tourist area. The study areas can easily be accessible within walking distance and connected with various modes of transportation and linkages. The analysis helped to identify issues and problems at tourism destinations in term of infrastructure and facilities. Among the issues found in term of safety, cleanliness, information and accessibility are taken into consideration. This research help to extend the service quality of facilities by constructing a user-friendly design of infrastructures and including sustainable based development to attract more tourists.